The efficacy of mirabegron in the treatment of urgency and the potential utility of combination therapy. Issue 8 (August 2018) - Andersson, Karl-Erik; Choudhury, Nurul; Cornu, Jean-Nicolas; Huang, Moses; Korstanje, Cees; Siddiqui, Emad; Van Kerrebroeck, Philip
Urgency is the prevalent and most bothersome symptom of overactive bladder (OAB) and the treatment of urgency is the primary objective in the management of OAB. Urgency has a major impact on other symptoms of OAB and culminates in an increased frequency of micturition and reduced volume voided, which may contribute to shorter intervals between the need to void. Antimuscarinic agents and mirabegron, a β3 -adrenoceptor agonist, constitute the main oral pharmacotherapeutic options for the treatment of urgency and other OAB symptoms. The reduction of urgency and other OAB symptoms significantly improve health-related quality of life. This review will explore the distinct mechanisms of action and effects of antimuscarinic agents and mirabegron, in relation to their effect on the pathophysiology of urgency. The review will also provide an overview of the various validated measurements of urgency and the numerous clinical trials regarding antimuscarinic agent monotherapy, mirabegron monotherapy, or combination treatment with mirabegron added on to the antimuscarinic agent solifenacin. A narrative review of the literature relating to pathophysiology of urgency, the validated measurements of urgency, and clinical trials relating to the pharmacological treatment of urgency. Antimuscarinic agent monotherapy, mirabegron monotherapy, or combination treatment with mirabegron added on to the antimuscarinic agent solifenacin statistically significantly reduce the symptoms of urgency compared with placebo. Combination therapy with mirabegron added on to solifenacin also statistically significantly reduces the symptoms of severe urgency compared with antimuscarinic agent monotherapy. A critique of the clinical benefits of combination therapy is also provided. Combination therapy provides an alternative treatment in patients with OAB that includes urgency who respond poorly to first-line monotherapy and who may otherwise often move on to more invasive treatments.